Circulating Adipokines in Healthy versus Unhealthy Overweight and Obese Subjects - Assim A. Alfadda (International Journal of Endocrinology)
It is now well established that not all obese subjects are at increased risk of cardiometabolic complications; such patients are termed the metabolically healthy obese. Despite their higher-than-normal body fat mass, they are still insulin sensitive, with a favorable inflammatory and lipid profile and no signs of hypertension. It remains unclear which factors determine an individual's metabolic health. Adipose tissue is known to secrete multiple bioactive substances, called adipokines, that can contribute to the development of obesity-associated complications. The goal of this study was to determine whether the circulating adipokine profiles differs between metabolically healthy and metabolically unhealthy overweight and obese subjects, thereby obtaining data that could help to explain the link between obesity and its related cardiometabolic complications. We defined metabolic health in terms of several metabolic and inflammatory risk factors. The serum adiponectin levels were higher in the healthy group and showed a positive correlation with HDL cholesterol levels in the unhealthy group. There were no differences between the two groups in the levels of serum leptin, chemerin and orosomucoid. Accordingly, adiponectin might play a role in protecting against obesity-associated cardiometabolic derangements. More studies are needed to clarify the role of different chemerin isoforms in this system.